Use of Resident-Origin Data to Define Nursing Home Market Boundaries - Jack Zwanziger; Dana B. Mukamel; Indridi Indridason (SAGE Publishing, 2002)
Previous studies of nursing home markets have assumed that a nursing home's market is coincident with the boundaries of the county in which it is located. We test this assumption by using the zip code of residence for Medicare beneficiaries admitted into a nursing home in New York state in the periods 1992-93 and 1996-97. We find that nursing homes located in urban areas have markets that are a fraction of the size of the county in which they are located. We calculate the Herfindahl-Hirschman Index (HHI) to measure the competitiveness of each nursing home's market. This shows that nursing home markets tend to be more concentrated than those that result from assuming countywide markets. These results suggest that studies of nursing home markets should not use counties as markets.